Report from Kenya’s Climate Smart Agriculture Multi-Stakeholder Platform (CSA MSP) Livestock Learning Platform meeting - Cramer, Laura K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The Programme for Climate-Smart Livestock Systems (PCSL) is an initiative designed to enable key actors in the livestock sector to increasingly include climate change adaptation and mitigation in their farming practices, sector strategies and investment projects. PCSL is financed by GIZ and commissioned by the Government of the Federal Republic of Germany. GIZ has commissioned the International Livestock Research Institute (ILRI) and the World Bank to implement the programme activities. ILRI’s programme activities are based in Kenya, Ethiopia and Uganda. One of the PCSL activities has been the creation of national Learning Platforms to support information exchange and dissemination of research findings to the relevant stakeholders. The Learning Platforms bring stakeholders together quarterly to discuss various topics. Due to the Covid- 19 pandemic and the resulting restrictions on travel and in-person gatherings, these meetings are now taking place online. In Kenya, the Learning Platform is operating through the existing Climate Smart Agriculture Multi- Stakeholder Platform (CSA MSP). A meeting held on Wednesday, 21st April 2021 showcased a presentation of a recent report on how the livestock sub-sector can be enhanced in the country’s Nationally Determined Contribution (NDC), new research findings to support development of country specific emissions factors from sheep and goats in Western Kenya, and a sneak preview of adaptation tracking protocols for the livestock sector that are under development (see Annex 1 for the full agenda). More than 40 participants were online for the session, representing ILRI, the Ministry of Agriculture, Livestock, Fisheries and Cooperatives (MOAFLC), non-governmental and civil society organizations, and private sector companies (see Annex 2 for a list of participants).